2016
DOI: 10.1097/txd.0000000000000632
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Broad Antigen HLA Mismatches, Eplet HLA Mismatches and Acute Rejection After Kidney Transplantation

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
(30 reference statements)
2
21
0
Order By: Relevance
“…Lachmann et al 9 showed in a cohort of 2787 adults with a kidney transplantation, with a mean follow‐up of 7.2 years that the occurrence of DSA (16%) is dependent on the eplet load, more eplets mismatches, higher incidents of DSA. In a cohort of 3449 adults observed for a similar period of time (3.4 years the median follow‐up), Nguyen et al 10 showed that 18% of the patients developed DSA and the median eplet load was 22.8 (higher than in our study) and the patients were evaluated only for HLA DR typing. In pediatric transplantation, we found two papers reporting eplet match in kidney transplantation.…”
Section: Discussionsupporting
confidence: 46%
“…Lachmann et al 9 showed in a cohort of 2787 adults with a kidney transplantation, with a mean follow‐up of 7.2 years that the occurrence of DSA (16%) is dependent on the eplet load, more eplets mismatches, higher incidents of DSA. In a cohort of 3449 adults observed for a similar period of time (3.4 years the median follow‐up), Nguyen et al 10 showed that 18% of the patients developed DSA and the median eplet load was 22.8 (higher than in our study) and the patients were evaluated only for HLA DR typing. In pediatric transplantation, we found two papers reporting eplet match in kidney transplantation.…”
Section: Discussionsupporting
confidence: 46%
“…In fact, it is well documented that HLA antibodies can be generated against an allele with only a single amino acid difference, such as in cases of allele level antibodies . Moreover, multiple cutoff values for eplet mismatch load are reported in different studies . Indeed, the data presented here demonstrate this exact limitation.…”
Section: Discussionmentioning
confidence: 76%
“…It is notable that only minor variations were found when comparing the ability of these different approaches to predict poor graft outcome (correlation ranging between R 2 of .85‐.96) . In addition, when different patient populations were studied (eg, pediatric vs adult; kidney vs lung), different cutoff values were reported, indicating the need to determine appropriate cutoff values for center‐specific populations before adopting any of these approaches. Significantly, in each of the cohorts, a high mismatch score was not universally associated with de novo HLA‐DSA generation or rejection and vice versa, suggesting that factors beyond number of mismatches play a role in determining the immunogenicity and antigenicity of donor/recipient mismatches.…”
Section: Introductionmentioning
confidence: 99%
“…Broad antigen HLA-DQ matching between each recipient and donor on the basis of serologic typing is available for the majority of kidney transplant recipients in the United Network for Organ Sharing (UNOS) registry (15). Using UNOS data, we sought to determine the effect of HLA-DQ matching on acute rejection and graft loss after kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%